Clustering properties of BzK-selected galaxies in goods-N: Environmental quenching and triggering of star formation at z ~ 2 - Lin, L.; Dickinson, M.; Jian, H.; Merson, A.; Baugh, C.; Scott, D.; Foucaud, S.; Wang, W.; Yan, C.; Yan, H.; Cheng, Y.; Guo, Y.; et al. (2012)
Using a sample of BzK-selected galaxies at z ~ 2 identified from the CFHT/WIRCAM near-infrared survey of GOODS-North, we discuss the relation between star formation rate (SFR), specific star formation rate (SSFR), and stellar mass (M *), and the clustering of galaxies as a function of these parameters. For star-forming galaxies (sBzKs), the UV-based SFR, corrected for extinction, scales with the stellar mass as SFRM a * with a = 0.74 ± 0.20 down to M * 109 M ?, indicating a weak dependence on the stellar mass of the SFR efficiency, namely, SSFR. We also measure the angular correlation function and hence infer the correlation length for sBzK galaxies as a function of M *, SFR, and SSFR, as well as K-band apparent magnitude. We show that passive galaxies (pBzKs) are more strongly clustered than sBzK galaxies at a given stellar mass, mirroring the color-density relation seen at lower redshifts. We also find that the correlation length of sBzK galaxies ranges from 4 to 20h -1Mpc, being a strong function of MK , M *, and SFR. On the other hand, the clustering dependence on SSFR changes abruptly at 2 × 10-9yr-1, which is the typical value for "main-sequence" star-forming galaxies at z ~ 2. We show that the correlation length reaches a minimum at this characteristic value, and is larger for galaxies with both smaller and larger SSFRs; a dichotomy that is only marginally implied from the predictions of the semi-analytical models. Our results suggest that there are two types of environmental effects at work at z ~ 2. Stronger clustering for relatively quiescent galaxies implies that the environment has started to play a role in quenching star formation. At the same time, stronger clustering for galaxies with elevated SSFRs (" starbursts") might be attributed to an increased efficiency for galaxy interactions and mergers in dense environments. © © 2012. The American Astronomical Society. All rights reserved.